Exploring the Structure and Language Features of Successful Business Letters: A Case Study of a Tour Travel Agency - Witono, Hudan Ahmad Dardiri; Nuriadi, Nuriadi; Mahyuni, Mahyuni (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Business letters play crucial roles in exchanging information, maintaining relationships, and creating markets in organizations. However, the gap between academic research and practical workplace application in business letter writing remains underexplored. This study analyzes the generic structure and linguistic features of successful English business letters—defined as those achieving their communicative and business objectives—in authentic professional contexts. Using a genre-based approach, fifty original business letters from a travel agent in West Nusa Tenggara (2021-2022) were examined. Results revealed that successful business letters follow a systematic structure: sender's address, recipient's address, opening greeting, body (2-3 focused paragraphs), and closing greeting, notably omitting the subject line. Four key linguistic features characterize these letters: formality (using formal vocabulary), practicality-professionalism (employing technical terminology), informativeness (using business-specific language to prevent misunderstandings), and politeness (utilizing modal verbs and courteous expressions). These findings bridge the gap between ESP theory and real-world practice, demonstrating that successful business letters adapt academic formats to meet practical business demands. The study provides evidence-based recommendations for business practitioners and ESP educators, contributing to effective business communication practices in authentic professional environments.